Liposomal Drug Delivery Systems: An Update Review - Samad, A.; Sultana, Y.; Aqil, M.
The discovery of liposome or lipid vesicle emerged from self forming enclosed lipid bi-layer upon hydration; liposome drug delivery systems have played a significant role in formulation of potent drug to improve therapeutics. Recently the liposome formulations are targeted to reduce toxicity and increase accumulation at the target site. There are several new methods of liposome preparation based on lipid drug interaction and liposome disposition mechanism including the inhibition of rapid clearance of liposome by controlling particle size, charge and surface hydration. Most clinical applications of liposomal drug delivery are targeting to tissue with or without expression of target recognition molecules on lipid membrane. The liposomes are characterized with respect to physical, chemical and biological parameters. The sizing of liposome is also critical parameter which helps characterize the liposome which is usually performed by sequential extrusion at relatively low pressure through polycarbonate membrane (PCM). This mode of drug delivery lends more safety and efficacy to administration of several classes of drugs like antiviral, antifungal, antimicrobial, vaccines, anti-tubercular drugs and gene therapeutics. Present applications of the liposomes are in the immunology, dermatology, vaccine adjuvant, eye disorders, brain targeting, infective disease and in tumour therapy. The new developments in this field are the specific binding properties of a drug-carrying liposome to a target cell such as a tumor cell and specific molecules in the body (antibodies, proteins, peptides etc.); stealth liposomes which are especially being used as carriers for hydrophilic (water soluble)anticancer drugs like doxorubicin, mitoxantrone; and bisphosphonate-liposome mediated depletion of macrophages. This review would be a help to the researchers working in the area of liposomal drug delivery.
Keywords: LIPOSOME; CHARACTERIZATION; SIZING OF LIPOSOMES; SURFACE HYDRATION; TARGETED SITE; PHOSPHOLIPIDS